PERBEDAAN UNSUR-UNSUR â€œMENYALAHGUNAKAN KEWENANGANâ€ DALAM PERATURAN PERUNDANG-UNDANGAN PERADILAN ADMINISTRASI DAN PERADILAN TINDAK PIDANA KORUPSI, DAN APAKAH KONSEKUENSINYA TERHADAP PERTANGGUNGJAWABAN PIDANA KORUPSI - Adnani, Adriani (Ensiklopedia Sosial Review, 2019)
"Abuse of authority" and "abuse of authority" is a term born of the doctrine of State Administrative Law and commonly used in the realm of law. Etymologically, the terms "abuse" and "abuse" are derived from two syllables "misuse". Misuse in the form of noun means the process, method, act of abusing; fraud, while "abuse" in the form of a verb is meant to do something that is not as it should; abuse. The term abuse / abusing in Dutch terms is known as misbruik which has similarities to the term missbrauch in German or misuse and abuse in English terms whose meaning is always associated with a negative thing which is abuse. So between the terms "abuse" and "abusing" there is no difference, "abuse" refers to the process, method, actions, while "abusing" refers to the action or implementation.